Linkages between agro-industry and small-scale agriculture in Guyana - Harvey, Ena C. (CEPAL SantiagoCL, 1996)
Looks at the linkages with a view to determining the types of products and forms of association that have the greatest potential to enchance the levels of productivity and income of small agricultural producers.